THE FAVORITE PERSONAL OBJECTS IN THE ADULTHOOD AND SENILITY. AN EMPIRIC APPROACH - Yuste Rossell, Nazario; González Almagro, Ignacio (Anales de Psicología / Annals of Psychology, 1998)
Concerning two age groups (348 adults and 303 senior citizens) and by means of a questionnaire based on one by Kamptner, Kayano and Peterson (1989), we examined what objects were preferred in infancy and adolescence and which are preferred now, if these change due to special circumstances, which of those now lacking are wanted and what feelings are perceived at their loss. It is intended to show, in a first approximation, if their exists an affinity for objects, and its meaning and importance during the whole human life cycle. The results show that neither marital status, locality nor cultural level influence preferences, however differences do appear in the kind of favorite things preferred by children and adolescents, also in those preferred by adults and older people (coinciding with works by Csikszentimihalyi and Rochberg-Halton, 1981; Sherman and Newman, 1977-78; Kamptner, Kayano and Peterson, 1989). Main reasons in order to prefer one oject or another during the life-span are age, generation cohort, gender and social influences. The study focuses on future investigations in which transcultural aspects will be considered, the overcoming or not of gender differences (given the present androgeny) and whether new technology will affect future generations of adults and senior citizens.